2009
DOI: 10.1039/b902765c
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted pyridazines as building blocks in novel supramolecular architectures

Abstract: A series of mono, 1,4-di and 1,3,5-tri 4-substituted 3,6-di(2-pyridyl)pyridazines were analyzed to evaluate the substituent and steric effects in the crystal packing.Renewed interest in pyridazine chemistry arises from the potential that they have shown in the formation of polynuclear coordination assemblies with diverse topologies including [2 Â 2] grids, 1 metallocryptand cages 2 and helices.3 One of the best studied compounds in this class is 3,6-di(2-pyridyl)pyridazine and its derivatives.4b The N-atoms pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…95 Varughese et al have studied a series of mono-1,4-di and 1,3,5-tri-4-substituted 3,6-di(2-pyridyl)pyridazines to evaluate the substituent and steric effects in the crystal packing (Scheme 41). 96 The three-dimensional architecture of the resulting assemblies was dependant of the substitution and the recognition pattern. The one-dimensional coordination polymer 207 exhibits as outstanding feature the rare structure of a meso-helix (Fig.…”
Section: Supramolecular Assembliesmentioning
confidence: 99%
“…95 Varughese et al have studied a series of mono-1,4-di and 1,3,5-tri-4-substituted 3,6-di(2-pyridyl)pyridazines to evaluate the substituent and steric effects in the crystal packing (Scheme 41). 96 The three-dimensional architecture of the resulting assemblies was dependant of the substitution and the recognition pattern. The one-dimensional coordination polymer 207 exhibits as outstanding feature the rare structure of a meso-helix (Fig.…”
Section: Supramolecular Assembliesmentioning
confidence: 99%
“…A synthetic protocol which can be extended to multiple systems is very attractive and new aromatic ligands generated by Diels-Alder cycloaddition have come to the fore in Ru(II) chemistry. [7][8][9][10] One development in copper chemistry has been the inclusion of stabilizing phosphine ligands, offering a significant improvement on the photophysical properties. McMillin and co-workers have demonstrated that bulky bidentate phosphines (such as POP = bis [2-(biphenylphosphino)phenyl]ether) inhibit the formation of quenching exciplexes, providing unusually long emission lifetimes and rather good quantum yields, typically in the green spectral window.…”
Section: Introductionmentioning
confidence: 99%
“…The 2-pyridyl moieties in phenyl-3,6-di(2-pyridyl)pyridazine, 1a , are in a trans,trans -arrangement with respect to the pyridazine heteroatoms and play no role in the hydrogen bond formation . This can be attributed to the orientation of the pyridyl rings toward an unfavorable sterically demanding environment resulting from the phenyl moiety.…”
Section: Resultsmentioning
confidence: 99%